2014
DOI: 10.1371/journal.pone.0109855
|View full text |Cite
|
Sign up to set email alerts
|

A Murine Inhalation Model to Characterize Pulmonary Exposure to Dry Aspergillus fumigatus Conidia

Abstract: Most murine models of fungal exposure are based on the delivery of uncharacterized extracts or liquid conidia suspensions using aspiration or intranasal approaches. Studies that model exposure to dry fungal aerosols using whole body inhalation have only recently been described. In this study, we aimed to characterize pulmonary immune responses following repeated inhalation of conidia utilizing an acoustical generator to deliver dry fungal aerosols to mice housed in a nose only exposure chamber. Immunocompetent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(55 citation statements)
references
References 40 publications
(66 reference statements)
2
46
0
Order By: Relevance
“…After examining miRNAs that had demonstrated the most significant changes following subchronic A. fumigatus exposure, IPA identified miR‐29a‐3p which targets two critical genes in the inflammatory response, Clec7a and TGF‐ β. Clec7A is important relative to conidia germination and align with previous studies that have reported A. fumigatus germination to elicit an inflammatory response due to the recognition of β‐glucan on the hyphal cell wall . Previous studies from our laboratory showed germination of A. fumigatus conidia in the lungs of mice exposed to viable A. fumigatus conidia . These results are further supported by increased Clec7A expression in the viable vs. HIC group at both time points.…”
Section: Discussionsupporting
confidence: 89%
“…After examining miRNAs that had demonstrated the most significant changes following subchronic A. fumigatus exposure, IPA identified miR‐29a‐3p which targets two critical genes in the inflammatory response, Clec7a and TGF‐ β. Clec7A is important relative to conidia germination and align with previous studies that have reported A. fumigatus germination to elicit an inflammatory response due to the recognition of β‐glucan on the hyphal cell wall . Previous studies from our laboratory showed germination of A. fumigatus conidia in the lungs of mice exposed to viable A. fumigatus conidia . These results are further supported by increased Clec7A expression in the viable vs. HIC group at both time points.…”
Section: Discussionsupporting
confidence: 89%
“…Short term A. fumigatus spore inhalation exposures (4 weeks) were found to induce an acute inflammation highlighted by a notable CD8 + IL‐17A + (Tc17) response that correlated with in vivo spore germination . In the present study, subchronic exposures (13 weeks) in naïve animals skewed the immune response towards an allergic phenotype resulting in significant expansion of diverse subpopulations of CD4 + T cells and Tc17 cells no longer detectable.…”
Section: Discussionmentioning
confidence: 47%
“…Notably, the repeated exposures of A. fumigatus spores resulted in a dose‐dependent and multifocal peribronchial and perivascular inflammation characterized by mononuclear phagocytes, granulocytes, and lymphocytes and concomitant epithelial mucus hypersecretion, goblet cell metaplasia, subepithelial fibrosis, and enhanced airway hyperresponsiveness (AHR). Interestingly, in contrast to the short course exposure, the pulmonary infiltrate was predominately consisted of CD4 + IL‐13 + T cells and an antifungal CD4 + IFN‐ß + IL‐17A + IL‐13 + T cell response, revealing a dynamic shift in the dysregulated immune response following subchronic exposure of inhaled fungi. Understanding the signals involved in the oscillation of these CD4 + T cell populations between antifungal/allergic Th1, Th2, Th17 phenotypes will provide a better understanding of the underlying pathways that contribute to the fungal association with allergic disease.…”
Section: Mechanisms Of Allergic Diseasementioning
confidence: 95%
“…To address these methodologic limitations, Buskirk et al developed an acoustical generator system (AGS) for delivering dry aerosolized fungal spores to mice housed in a multi‐animal exposure chamber. Aerosolized spores are delivered into a nose‐only inhalation chamber, where mice inhale the spores.…”
Section: Mechanisms Of Allergic Diseasementioning
confidence: 99%
See 1 more Smart Citation